2013
DOI: 10.1027/2192-0923/a000035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Behavioral Styles of Fear of Flying

Abstract: According to the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV), fear of flying is a specific situational phobia, but it has a heterogeneous character because it can be influenced by many other fears. Attention toward (monitoring) or away from (blunting) threatening information is influenced by people’s control of voluntary attention. In our online questionnaire study, 9,166 subjects (age 17–70 years) were selected for participation. The Flight Anxiety Modality (FAM) questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…When airplanes were first commercialized, air travel could be hazardous because many of the safety precautions travelers have today were not established. Even as safety has increased, fear of flying (aviophobia) often remains for many travelers (van Almen & van Gerwen, 2013). Although not all apprehensive flyers meet the criteria for a specific phobia, nearly 10%-40% of the general population in industrial ized countries have a fear of flying, and about 20% of the flying population have continuous or mild apprehension about flying but fly anyway (Gerwen, Spinhoven, Dyck, & Diekstra, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…When airplanes were first commercialized, air travel could be hazardous because many of the safety precautions travelers have today were not established. Even as safety has increased, fear of flying (aviophobia) often remains for many travelers (van Almen & van Gerwen, 2013). Although not all apprehensive flyers meet the criteria for a specific phobia, nearly 10%-40% of the general population in industrial ized countries have a fear of flying, and about 20% of the flying population have continuous or mild apprehension about flying but fly anyway (Gerwen, Spinhoven, Dyck, & Diekstra, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Participants are allowed and encouraged to elaborate as much as they want.) Gerwen, 2013). Although not all apprehensive flyers meet the criteria for a specific phobia, nearly 10%-40% of the general population in industrial ized countries have a fear of flying, and about 20% of the flying population have continuous or mild apprehension about flying but fly anyway (Gerwen, Spinhoven, Dyck, & Diekstra, 1999).…”
Section: Appendix Amentioning
confidence: 99%
“…Regardless of these diagnostic considerations a number of stimuli have been demonstrated to cue threat-perception and anxiety response in flying phobia including a variety of external stimuli associated with flying (e.g., planes, safety briefings, cabin announcements) and interoceptive information (e.g., heart-rate, breathing difficulties; van Almen and van Gerwen, 2013 ). However, the nature of the internal and external cues that most typically trigger threat perception in flying phobia has yet to be fully understood.…”
Section: Perceived Threat and Related Cuesmentioning
confidence: 99%
“…However, to date, there has been very limited consideration of the role of selective attention in maintaining flying phobia and we identified only one study that directly investigated attention in relation to the fear of flying. This single study, conducted by van Almen and van Gerwen ( 2013 ), reported that increased monitoring of threat cues (quantified by a general self-report measure of responses to hypothetical non-flying stressful situations) was associated with higher self-reported flight anxiety. This study was not specific to flying-related material and measured participants' perception that they would engage in the intentional deployment of attention (i.e., monitoring or avoiding threat-relevant information), which may be conceptualized as being distinct from the automatic allocation of attention toward threat stimuli observed across anxiety disorders.…”
Section: Attentionmentioning
confidence: 99%
See 1 more Smart Citation